Orbital inflammatory disease in a primarily black patient population - Kabarriti, Gabriel; Elsayed, Ali; Moustafa, Giannis A.; Hodgson, Nickisa (Frontiers in Ophthalmology, 2025)
PurposeThe purpose of this study is to characterize orbital inflammatory disease (OID) in a primarily Black patient population, examining their demographics, presentations, workup, treatment, and outcome.MethodsA retrospective study was performed from January 2005 to June 2022 at two academic institutions in Brooklyn, NY. Patients included met criteria for one of the following OID conditions: non-specific orbital inflammation; nonbacterial dacryoadenitis; Tolosa-Hunt; orbital myositis; definite, possible, or probable IgG4-related ophthalmic disease; and sclerosing orbital inflammation. Data reviewed included orbital inflammatory labs, imaging, pathology, and treatment. Treatment was considered successful if a patient had complete resolution of symptoms.ResultsThirty-nine patients met criteria for this study. 35.9% were diagnosed with dacryoadenitis, 28.2% with NSOI, 12.8% with myositis, 5.1% with possible IgG-ROD, 7.7% with probable IgG4-ROD, 7.7% with Tolosa Hunt, and 2.6% with sclerosing OI. 91% were started on steroids; 12.8% required transition to steroid-sparing therapy. 85% had a successful outcome with a resolution of symptoms.ConclusionsThis study characterizes OID in a Black patient population and compares it to prior studies done on OID. Research on underrepresented patient populations is needed to understand differences in disease presentation and improve patient outcomes.